ANALISA PENGARUH DEBT TO EQUITY RATIO (DER) DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR BEI 2013-2017 - Pujiati, Herni; Iswati, Sri; Subagio, Mochammad (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2024)
The research was conducted with the aim of analyzing ang know whether the Debt To Equity Ratio and sales growth have a simultaneous effect on stock prices as well as the effect of the variable Debt To Equity Ratio and partial sales growth on stock prices in the food and beverage sub-seector companies registered with PT Bursa Efek Indonesia 2013- 2017. The research method uses quantitative secondary methods. This population in this study is a food and beverage sub-sector company registered with PT. Bursa Efek Indonesia 2013-2017 as many as 25 companies. The sample of this study used purposive sampling technique. The number of samples that meet the criteria for the number of 5 companies. The variable used in this study Debt To Equity Ratio (DER), sales growth as the independent variable and stock price as the dependent variable. The analysis technique used is the classicassumption test, which includes normality test, multicollinearity test, autocorrelation test and heterokedastisidas test. Multiple regression analysis, hypothesis testing and coefficient of determination. The result of the T test show partially the variable debt to equity ratio has a significant effect on stock prices, while sales growth does not effect stock prices. The result of the F test show simultaneously the debt to equity ratio and stock price growth does not significantly influence stock prices. And the result of the study of the coefficient of determination show from the adjusted R-Square value of 0,209%.Keywords : Debt To Equity Ratio, Sales Growth, Stock Price.